Resolution of paraneoplastic palmoplantar keratoderma after treating mixed serous neuroendocrine tumor of the pancreas: a case report and literature review (Dermatology Reports, 2024)
Palmoplantar keratodermas (PPKs), also known as ‘keratosis palmaris et plantaris’, are a heterogeneous group of disorders characterized by abnormal thickening of the epidermal skin of the palms and soles leading to hyperkeratosis. It could be acquired or hereditary. Acquired PPK often occurs as a paraneoplastic syndrome as well as a stigma of other dermatoses. We report a rare case of paraneoplastic PPK secondary to mixed neuroendocrine tumor of the pancreas with complete remission after surgical excision of the cancer.